Ephemeral Emotional Resonance: User-Perceived Functional Value Leading to Short-Form Video Use - Xinzhou Xie; Yanjun Lin; Qiyu Bai (Behavioral Sciences)
With the rapid development of short-form videos, more and more people have gained a deep understanding of the functional value of short-form videos. Based on structuration theory, this paper explores the reasons why users use short-form videos. The authors conducted a questionnaire survey on 2613 Chinese short video users, and found that bridging social capital played a mediating role between users’ perceived functional value of short-form videos and their use of short-form videos. In addition, internet self-efficacy played a moderating role. This finding not only enhances our understanding of the value of short-form videos and users’ relational needs, but also highlights the crucial role of self-efficacy in users’ engagement with this new medium.